2015
DOI: 10.4236/ape.2015.54027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Video Modeling Process on Teaching/Learning Hurdle Clearance Situations on Physical Education Students

Abstract: The purpose of this study was to investigate the difference between two pedagogical methods in teaching/learning hurdle clearance such as the traditional learning method which was based on verbal feedback and the new technology through motion analysis and video modeling which was based on self-modeling, expert modeling and model's superposition. Twenty-seven sports science students took part in this study. Modeling group composed of 15 students and traditional group of 12 students. Both groups participated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…Yet, several studies have shown the potential of using VFB in PE teaching to improve the effectiveness of demonstrations (Lhuisset and Margnes 2014) for enhancing skill learning, knowledge and game understanding (Blomqvist, Luhtanen, and Laakso 2001;Koekoek et al 2018). Studies seeking to assess the specific effect of VFB on motor skill acquisition in a PE setting at different education levels have shown its effectiveness when it was coupled with teacher feedback (Mérian and Baumberger 2007;Uhl and Dillon 2009;Potdevin et al 2013;Amara et al 2015;Kretschmann 2017). No effects have been observed when VFB was provided without the instruction as well (Madou and Cottyn 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, several studies have shown the potential of using VFB in PE teaching to improve the effectiveness of demonstrations (Lhuisset and Margnes 2014) for enhancing skill learning, knowledge and game understanding (Blomqvist, Luhtanen, and Laakso 2001;Koekoek et al 2018). Studies seeking to assess the specific effect of VFB on motor skill acquisition in a PE setting at different education levels have shown its effectiveness when it was coupled with teacher feedback (Mérian and Baumberger 2007;Uhl and Dillon 2009;Potdevin et al 2013;Amara et al 2015;Kretschmann 2017). No effects have been observed when VFB was provided without the instruction as well (Madou and Cottyn 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Ten weeks of exercises in the field of hurdle sprint race is a sufficient period to evaluate the ,,post-training" effects (Amara et al, 2015).…”
Section: Protocolmentioning
confidence: 99%
“…A didactical tool that may support the mutual agreement and accuracy of students' perceptions during DI is reviewing video footage from students' actual game play. In general, researchers have claimed beneficial effects of digital video in PE and sports, especially when used for video-modeling (Amara et al 2015;Sani and Khan 2017) and assessment for learning such as feedback (O'Loughlin, Chróinín, and O'Grady 2013; Kok and van der Kamp 2018;Palao et al 2015;Van der Kamp et al 2015;Weir and Connor 2009). This research has largely focused on supporting the learning of motor skills or techniques, and only few studies have investigated digital video to enhance game understanding (e.g.…”
Section: Digital Video and Debates In Game-based Settingsmentioning
confidence: 99%